A genomic perspective of the pink-headed duck Rhodonessa caryophyllacea suggests a long history of low effective population size. Issue 1 (December 2017) - Ericson, Per; Qu, Yanhua; Blom, Mozes; Johansson, Ulf; Irestedt, Martin
Abstract The first molecular phylogenetic hypothesis for the possibly extinct pink-headed duckRhodonessa caryophyllacea unambiguously shows that it belongs to the pochard radiation that also includes the generaAythya andNetta . It is the sister to all modern-day pochards and belongs to a lineage that branched off from the others more than 2.8 million years ago.Rhodonessa caryophyllacea is believed to never have been common in modern time and we show this has probably been the situation for as long as 100, 000 years. Our results suggest that their effective population size varied between 15, 000 and 25, 000 individuals during the last 150, 000 years of the Pleistocene. The reasons behind this are largely unknown as very little is known about the life-history and biology of this species. Presumably it is due to factors related to feeding or to breeding, but we may never know this for sure.